2004
DOI: 10.1104/pp.104.043315
|View full text |Cite
|
Sign up to set email alerts
|

Maize Starch-Branching Enzyme Isoforms and Amylopectin Structure. In the Absence of Starch-Branching Enzyme IIb, the Further Absence of Starch-Branching Enzyme Ia Leads to Increased Branching

Abstract: Previous studies indicated that the deficiency of starch-branching enzyme (SBE) Ia in the single mutant sbe1a::Mu (sbe1a) has no impact on endosperm starch structure, whereas the deficiency of SBEIIb in the ae mutant is well known to reduce the branching of starch. We hypothesized that in maize (Zea mays) endosperm, the function of SBEIIb is predominant to that of SBEIa, and SBEIa would have an observable effect only on amylopectin structure in the absence of SBEIIb. To test this hypothesis, the mutant sbe1a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 35 publications
7
74
0
2
Order By: Relevance
“…Interestingly, loss of SBEI activity in monocots and dicots has minimal apparent effects on starch synthesis and composition (45), although in a study by Yao et al, loss of SBEI from a SBEIIbdeficient background in maize was shown to cause increased branching of amylopectin. Yao et al (46) postulated that this result was suggestive of a regulatory role for SBEI in influencing other SBE isoforms. Indeed, physical interactions between SBEI and SBEIIb have been reported in cereal endosperm amyloplasts (see later section).…”
Section: Tablementioning
confidence: 92%
“…Interestingly, loss of SBEI activity in monocots and dicots has minimal apparent effects on starch synthesis and composition (45), although in a study by Yao et al, loss of SBEI from a SBEIIbdeficient background in maize was shown to cause increased branching of amylopectin. Yao et al (46) postulated that this result was suggestive of a regulatory role for SBEI in influencing other SBE isoforms. Indeed, physical interactions between SBEI and SBEIIb have been reported in cereal endosperm amyloplasts (see later section).…”
Section: Tablementioning
confidence: 92%
“…Mutant lines defective for SBEI, IIa, and IIb in maize (Stinard et al, 1993;Blauth et al, 2001Blauth et al, , 2002Yao et al, 2004) and rice (Oryza sativa; Nishi et al, 2001;Nakamura, 2002;Satoh et al, 2003) were isolated and analyzed for their ability to synthesize starch. The absence of SBEI in both plants has little or no impact on starch that accumulates in the endosperm, while the absence of SBEIIb leads to the synthesis of a modified amylopectin with a strong decrease in the number of short chains and an increase in the number of long chains.…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study showed that SBEI transfers longer chains (DP ≥ 16) and has a higher affinity for amylose, while SBEII transfers shorter chains (DP ≤ 12) and appears to have a higher affinity for amylopectin [45]. However, in maize endosperm the amylopectin CLD is not affected by a deficiency in SBEI activity, although a further loss of SBEIIb causes increased branching, suggestive of a regulatory role for SBEI in influencing other SBEs [77,78]. This is supported by the observation of the physical interaction between SBEI and SBEIIb in the wheat endosperm amyloplast [71].…”
Section: Starch-branching Enzymes (Sbes)mentioning
confidence: 99%